2021
DOI: 10.3892/ijmm.2021.5047
|View full text |Cite
|
Sign up to set email alerts
|

Schizandrin A can inhibit non‑small cell lung cancer cell proliferation by inducing cell cycle arrest, apoptosis and autophagy

Abstract: Schizandrin A (SchA) can be extracted from the vine plant Schisandra chinensis and has been reported to confer various biologically active properties. However, its potential biological effects on non-small cell lung cancer (NSCLC) remain unknown. Therefore, the present study aims to address this issue. NSCLC and normal lung epithelial cell lines were first treated with SchA. Cell viability and proliferation were measured using CellTiter-Glo Assay and colony formation assays, respectively. PI staining was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…Our hypothesis can be indirectly validated because there studies have demonstrated the antitumor effects of these drugs. For example, Zhu et al found schizandrin A treatment reduced viability, inhibited proliferation and induced cell cycle arrest and apoptosis of NSCLC cells [ 73 ]. Bae reported that higher foliate levels can decrease lung cancer risk in men (odds ratios = 0.82) and former smokers (odds ratios = 0.7) [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis can be indirectly validated because there studies have demonstrated the antitumor effects of these drugs. For example, Zhu et al found schizandrin A treatment reduced viability, inhibited proliferation and induced cell cycle arrest and apoptosis of NSCLC cells [ 73 ]. Bae reported that higher foliate levels can decrease lung cancer risk in men (odds ratios = 0.82) and former smokers (odds ratios = 0.7) [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, clarifying the mechanism of programmed cell death can provide more possibilities for clinical treatment of cancer. For example, some studies have found that Schizandrin A can inhibit the proliferation of nonsmall cell lung cancer and breast cancer cells by inducing apoptosis (38,39). Meanwhile, Badgley et al (40) found that deletion of SLC7A11 induced tumor-selective ferroptosis and inhibited Pancreatic ductal adenocarcinoma growth.…”
Section: Figurementioning
confidence: 99%
“…Apoptosis is often accompanied by mitochondrial damage, and the decrease in MMP is a sign of mitochondrial damage (Zhu et al. 2021 ). To further explore whether CBG caused mitochondrial damage, we measured MMP, interestingly, MMP decreased ( Figure 4(A,B) ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, decreased MMP is a common sign of mitochondrial damage (Zhu et al. 2021 ). Mitochondria are the main sites of ROS, and massive ROS production may reflect mitochondrial damage.…”
Section: Discussionmentioning
confidence: 99%